Teaching Radically with Koch Money - Colson, Dan (Radical Teacher, 2018)
This essay narrates my experiences applying for a grant from my university’s Koch Center for Leadership and Ethics, and teaching the redesigned Survey of Later American Literature the grant funded. In it, I explore the Koch Center’s rhetoric, focusing especially on the space between their putative neutrality and their clear embrace of right-wing definitions of freedom. I detail my grant proposal, addressing primarily my methods for redeploying their language about “leadership,” “ethics,” and “freedom” in order to echo their putative neutrality while allowing myself room to foreground their circumscribed notions of “freedom.” Then, I outline the course I redesigned with the Koch Center’s funds, addressing both the course’s content and its pedagogical strategies. In closing, this essay offers some thoughts about how we might resist higher education’s seemingly inexorable shift rightward by reshaping the language and emphases of organizations like the Koch Center, ultimately suggesting we combat these neoliberal tendencies by battling them directly on the ground of “freedom.”